A bibliometric and visualization analysis of glucocorticoid-induced osteoporosis research from 2012 to 2021 - Jiang, Buchan; Feng, Chengyao; Li, Chenbei; Tu, Chao; Li, Zhihong (Frontiers in Endocrinology, 2022)
Introduction: Glucocorticoid-induced osteoporosis (GIOP) is the most common cause of secondary osteoporosis. Although many studies related to GIOP have been published, there was no bibliometric analysis in this field. This study aimed to investigate the research trends on GIOP by using bibliometric analysis. Materials and Methods: All data were collected from the Web of Science Core Collection (WoSCC). All original research articles regarding GIOP from 2012 to 2021 were retrieved. CiteSpace was used to analyze the distribution of countries, institutions, journals, authors, and keywords. We revealed hotspots and trends in the field by drawing co-occurrence keyword maps and identifying burst keywords. Results: From 2012 to 2021, 685 relevant articles were published, with a peak in 2018 in the annual number of publications. China and McMaster University were the leading country and institution in this field with 208 and 12 publications, respectively. Osteoporosis International was the journal with the most studies, while Journal of Bone and Mineral Research was the most cited journal. “Bone mineral density”, “fracture”, “postmenopausal women”, “prevention” and “therapy” were the most high-frequency keywords, while “bone mineral density”, “bisphosphonate” and “metabolism” were the top high-centrality keywords. Conclusion: The results from this bibliometric study provided insight into the status and research trends in GIOP of the past decade, which could help researchers quickly determine the current hotspots and frontier trends in this field.